2016
DOI: 10.1155/2016/9291412
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Function Method Roadway Section Design of the Soft Coal Seam

Abstract: As for the sophisticated advanced support technique of vertical wall semicircle arch roadway in the three-soft coal seam, a design of flat top U-shape roadway section was put forward. Based on the complex function method, the surrounding rock displacement and stress distribution laws both of vertical wall semicircle arch roadway and of flat top U-shape roadway were obtained. The results showed that the displacement distribution laws in the edge of roadway surrounding rock were similar between the two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…It is confirmed that the lithology of the surrounding rock and the size of the roadway section are important factors affecting the fracture range of the surrounding rock [25]. The mechanism and influencing factors of four types of kick drums, including squeeze-fluid kick drum, flexurally folded kick drum, shear dislocation kick drum and water-expandable kick drum, were analyzed [26]. On the basis of theoretical analysis, a support design scheme was proposed [27], and an integral closed support was constructed with active supports such as bolts, anchor cables and grouting as the main body [12,13,28,29].…”
Section: Introductionmentioning
confidence: 92%
“…It is confirmed that the lithology of the surrounding rock and the size of the roadway section are important factors affecting the fracture range of the surrounding rock [25]. The mechanism and influencing factors of four types of kick drums, including squeeze-fluid kick drum, flexurally folded kick drum, shear dislocation kick drum and water-expandable kick drum, were analyzed [26]. On the basis of theoretical analysis, a support design scheme was proposed [27], and an integral closed support was constructed with active supports such as bolts, anchor cables and grouting as the main body [12,13,28,29].…”
Section: Introductionmentioning
confidence: 92%
“…Using a complex function, a stress distribution function was established, and the distribution characteristics of the surrounding rock stress field were determined, which could be instrumental in improving tunnel design and construction practices. Tu, S et al [10] explored the design of a flat-top U-shaped section for mining roadways in three-soft coal seams based on the complex function method, presenting the geometric parameters of such design. This work helps in addressing the challenges faced in roadway support in such coal seams, making a contribution toward safer and more efficient mining operations.…”
Section: Introductionmentioning
confidence: 99%